Analisis Standar Operasional Prosedur (SOP) Funding dan Financing Melalui Implementasi Konsep Good Corporate Governance (GCG) di Koperasi Syariah Talun (STAI Attanwir) - Syaifudin, Ahmat Arif (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Standard Operating Procedures (SOP) have an important role in the activities carried out by Sharia Cooperatives because they are guidelines that are used as the basis for every activity or work procedure that is carried out. The SOP applied to the Koperasi Syariah Talun (STAI Attanwir) is aimed at funding and financing activities, both of which are the main activities found in the Sharia Cooperative, so the role of the SOP is very important so that these activities can run optimally. Each standardized SOP already contains a series of work producers which include the rights and obligations that must be carried out by members and managers in accordance with the job description that has been given. In addition to compliance with SOPs, Sharia Cooperatives also implement the concept of Good Corporate Governance (GCG) which regulates its governance and operational management. The SOP and GCG that are formed are a continuity that aims to improve the performance of Sharia Cooperatives so that both must go hand in hand. The purpose of this study is to analyze the SOP and implementation of GCG in the Koperasi Syariah Talun (STAI Attanwir). The method used in this research is qualitative with data collection techniques, namely observation, interviews, and documentation. From the research that the researchers did, the Koperasi Syariah Talun (STAI Attanwir) has implemented SOPs and implemented GCG although in its operations there are still obstacles, but overall compliance with SOP and GCG is able to improve the performance of the Koperasi Syariah Talun (STAI Attanwir).